Identification of Respondent Characteristics and Relationship of Clinical Manifestations with Chest Radiograph Lesion in Pulmonary Tuberculosis Patients at Aloei Saboe Hospital - Elen Lukum; Nanang Roswita Paramata; Moh Rizal F S Sadjar (Universitas Negeri Gorontalo, 2023)
Introduction: Tuberculosis (TB) is an infectious infectious disease caused by Mycobacterium tuberculosis. This study aimed to determine the relationship between clinical manifestations and the results of chest radiographs in adult pulmonary TB patients at Aloei Saboe Hospital.Method: The research design used in this study was cross-sectional by examining the relationship between clinical manifestations and chest radiography results in adult pulmonary TB patients at Aloei Saboe Hospital from October to November 2022. The population of this study was adult pulmonary TB patients using accidental sampling as a sampling technique. The research instrument used was the medical record which contained the patient's anamnesis status and the results of the chest radiography examination. The relationship between variables was then analyzed using the Kolmogorov-Smirnov test.Results: Of the 44 samples, the most common clinical manifestations were dyspnea and chest pain in 12 patients (26.67%). The most chest radiographic results were fibrotic in 21 patients (47.7%). According to the American Thoracic Association (ATA) classification, extensive lesions were predominantly found in 21 patients (47.7%). There was an association between productive cough and chest radiography results (p=0.012). Meanwhile, chest radiographs were not associated with productive cough, hemoptoe, and dyspnea.Conclusion: There is a relationship between productive cough and chest radiography lesions. Further study may determine samples for research that are minimally biased so that the results obtained are more representative of the population.